Acute hypoadrenocorticism (adrenal crisis) in the dog: a report on six clinical cases - KASABALIS (Δ. ΚΑΣΑΜΠΑΛΗΣ) D.; SOUBASIS (Ν. ΣΟΥΜΠΑΣΗΣ) N.; PARDALI (Δ. ΠΑΡΔΑΛΗ) D.; SAVAS (Ι. ΣΑΒΒΑΣ) I.; PAVLIDOU (Κ. ΠΑΥΛΙΔΟΥ) K.; PETANIDES (Θ.Α. ΠΕΤΑΝΙΔΗΣ) T. Α.; PAPADIMITRIOU (Δ. ΠΑΠΑΔΗΜΗΤΡΙΟΥ) D.; VARLAMI (Β. ΒΑΡΛΑΜΗ) V.; KOUTINAS (Α. ΚΟΥΤΙΝΑΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Medical records of six dogs admitted with acute hypoadrenocorticism were reviewed. All 6 animals were bradycardic and had prolonged capillary refilling time. Hypothermia was detected in 5/6 animals. Clinicopathological evaluation on admission revealed anemia (3/6 dogs), increased (2/6) and normal (2/6) lymphocyte and eosinophil counts, azotemia and hyperkalemia (6/6), hyponatremia, in 5/6 dogs in which sodium was measured with a sodium (Na) : potassium (K) ratio lower than 24, hypoglycemia (2/6) and hypercalcemia, hypocholosterolemia, increased serum alkaline phosphatase and alaninoaminotransferase activities, one dog each. Urine specific gravity was lower than 1025 in 4 dogs. Thoracic radiographs and abdominal ultrasonography disclosed microcardia (2/6), pleural effusion (2/6) and ascites (1/6). Two dogs (2/6), also, presented atrial standstill or atrioventricular block, detected on electrocardiograms. In all 6 animals emergency treatment included the use of intravenous normal saline and glucocorticoids (dexamethasone) immediately after the completion of an ACTH stimulation test with tetracosactide. Two dogs died, one during the 1st day and the other on the 4th day of hospitalization, the latter after the sudden appearance of severe hemorrhagic gastroenteritis. Hospitalization time in the remaining 4 dogs ranged from 3 to 10 days. Prolongation of hospitalization was associated with worsening of anemia, hypoalbuminemia, neurologic complications and non-responsive azotemia. Four dogs (4/6) were discharged on oral prednisolone and fluodrocortisone, but one died after a week for unknown reasons. Acute hypoadrenocorticism is a life threatening condition requiring emergency treatment for a successful outcome. Its inclusion in the differential diagnosis of canine emergencies, presented with acute weakness and gastrointestinal signs, is mandatory, but for its confirmation a complete laboratory and, most importantly, an ACTH stimulation test are always required.